IMPLIKASI PENGATURAN PENANGANAN DAMPAK SOSIAL KEMASYARAKATAN DALAM RANGKA PENYEDIAAN TANAH UNTUK PEMBANGUNAN NASIONAL DI IBU KOTA NUSANTARA - Masyita, Nuriah; Al Hidayah, Rahmawati; Subroto, Aryo; Harjanti, Wiwik; Nugroho, Sulung; Asufie, Khairunnisa Noor (Jurnal Ilmiah Advokasi, 2025)
Presidential Regulation No. 78 of 2023 on the Amendment to Presidential Regulation No. 62 of 2018 on the Handling of Societal Impacts in the context of Land Provision for National Development has been enacted. Community social impact in this study is land controlled by the community used for national development, both national strategic projects and non-national strategic projects. This research aims to see the implementation of the regulation on the handling of community social impacts in the Archipelago's capital city and the legal consequences on residents' land rights. The research method used is a social legal reserch approach by considering the contribution of doctrinal research by adding factors outside the norms, namely social facts, legal practices and all that influence them. The results of the study explain that the provision of compensation in Presidential Regulation Number 78 of 2023 concerning Handling Community Social Impacts in the Context of Providing Land for National Development is given to residents who do not have a right base and if there is compensation given in this case there are differences in Law Number 2 of 2012 concerning Land Acquisition for Development for Public Interest. The issuance of Presidential Regulation No. 78 of 2023 on Handling Community Social Impacts that the land rights of residents affected by development do not exist and are not recognised, so this shows that affected residents lose their land rights. The issuance of Presidential Regulation No. 78 of 2023 concerning Handling of Community Social Impacts that the land rights of residents affected by development do not exist and are not recognised, so this shows that affected residents lose their land rights and there is no deliberation to determine the amount of compensation, so there is no agreement in determining the amount of compensation for affected communities. The implementation of Community Social Impact Handling in the Framework of Land Provision for National Development in terms of providing compensation without recognition of land rights has the potential to remove people’s basic rights to land, especially residents affected by development projects run by the government.Keywords: Land Provision; National Development; Compensation